Corrective Osteotomy of Upper Extremity Malunions Using Three-Dimensional Planning and Patient-Specific Surgical Guides: Recent Advances and Perspectives - Saravi, Babak; Lang, Gernot; Steger, Rebecca; Vollmer, Andreas; Zwingmann, Jörn (Frontiers in Surgery, 2021)
Malunions of the upper extremity can result in severe functional problems and increase the risk of osteoarthritis. The surgical reconstruction of complex malunions can be technically challenging. Recent advances in computer-assisted orthopedic surgery provide an innovative solution for complex three-dimensional (3-D) reconstructions. This study aims to evaluate the clinical applicability of 3-D computer-assisted planning and surgery for upper extremity malunions. Hence, we provide a summary of evidence on this topic and highlight recent advances in this field. Further, we provide a practical implementation of this therapeutic approach based on three cases of malunited forearm fractures treated with corrective osteotomy using preoperative three-dimensional simulation and patient-specific surgical guides. All three cases, one female (56 years old) and two males (18 and 26 years old), had painful restrictions in range of motion (ROM) due to forearm malunions and took part in clinical and radiologic assessments. Postoperative evaluation of patient outcomes showed a substantial increase in range of motion, reduction of preoperatively reported pain, and an overall improvement of patients’ satisfaction. The therapeutic approach used in these cases resulted in an excellent anatomical and functional reconstruction and was assessed as precise, safe, and reliable. Based on current evidence and our results, the 3-D preoperative planning technique could be the new gold standard in the treatment of complex upper extremity malunions in the future.